Cost-effectiveness of hormone replacement therapy (HRT) Compared to isoflavones in post-menopausal osteoporosis - Bolaños Díaz, Rafael (2009)
Background: Since the current medical recommendation for hormone replacement therapy (HRT) states that the most effective dosing schedules for the shortest time periods must be used, isoflavone compounds have become an interesting alternative, considering they have a good effect on bone mass, and this may be directly related with a reduction in fracture risk.Objective: 1) To determine if isoflavone-based therapy has a better cost-effectiveness (c-e) ratio compared to that of HRT; 2) to determine the incremental c-e ratio; and 3) to determine the sensitivity of our assessment uysing univariate and bivariate tests and also measuring changes in therapy adherence.Material and methods: Effectiveness was defined as avoided fracture cases for both therapeutic interventions. Costs were measured considering real expenses from the patients perspective (societal), reviewing clinical records from patients treated for osteoporosis. An outpatient care flowchart from Arzobispo Loayza National Hospital (Lima) was used. The analytic horizon for this study was two years.Results: The expected effectiveness values for each treatment were as follows: 29 cases of avoided fractures out of 100 patients increasing their bone mineral density using isoflavone compunds, and 34 cases of avoided fractures out of 100 patients increasing their bone mineral density using HRT. Regarding costs, for the first two years of treating a hypothetical cohort including 100 women that increased their bone mineral density, total costs may reach S/. 386,800 and S/. 290,000, for HRT and isoflavones, respectively. For a hypothetical cohort of 100 women with no increase in their bone mineral density, total costs may reach s/. 1,000,000 (S/. 10,000 per case) assuming that no fractures may be avoided in this group. The calculated cost-effectiveness ratio for isoflavones is S/. 11,437 and for HRT it is S/. 12,602. This result indicates that isoflavone therapy for postmenopausal osteoporosis is slightly better compared with HRT considering cost-effectiveness. The incremental c-e analysis indicates that the additional expenses for each avoided fracture case with HRT is S/. 19,360 in a 2-year analytic horizon.Conclusion: According to the results of this study, isoflavone therapy is slightly better than HRT with respect to cost-effectiveness considering every level of treatment adherence. Univariate and bivariate sensitivity analyses showed a short modification margin for reversing the differences between both cost-effectiveness values.